2010
DOI: 10.1177/008124631004000203
|View full text |Cite
|
Sign up to set email alerts
|

Piaget, Vygotsky, and the Cultural Development of the Notions of Possibility and Necessity: An Experimental Study among Rural South African Learners

Abstract: I employ the theories of Vygotsky and Piaget in analysing the modes of experimental task performance in order to elaborate on the role that cultural content plays in the development and functioning of the notions of possibility and necessity. I challenge the notion of cognitive lag that has hitherto pervaded explanations of the development of subjects from non-industrialised, diverse socio-cultural settings. A Piagetian experimental task, comprising half circles of contrasting colours, is used in the investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
4
0
3
Order By: Relevance
“…The predominant mode of task response -where the participants grouped the objects appropriately in categorical terms and used abstract, but functional reasons to justify their classification -does not seem inconsistent with their practical conditions of learning and cognitive development in the schooling context where they do not normally acquire abstract forms of thinking and problem-solving through classroom learning (cf. Muthivhi, 2010;Muthivhi, 2008b).…”
Section: Resultsmentioning
confidence: 99%
“…The predominant mode of task response -where the participants grouped the objects appropriately in categorical terms and used abstract, but functional reasons to justify their classification -does not seem inconsistent with their practical conditions of learning and cognitive development in the schooling context where they do not normally acquire abstract forms of thinking and problem-solving through classroom learning (cf. Muthivhi, 2010;Muthivhi, 2008b).…”
Section: Resultsmentioning
confidence: 99%
“…Volviendo a los resultados obtenidos, en relación con el grupo de los niños, pudo observarse una producción taxonómica significativamente menor a la de los adultos jóvenes, en consonancia con otras investigaciones que hacen referencia a este patrón (Muthivhi, 2010). Al respecto, como ya fue mencionado, autores clásicos como Piaget y Vigotsky señalan que el conocimiento taxonómico es inestable en los niños y se robustece después de comenzada la educación formal, lo que lo convierte en el tipo de respuesta predominante en los estudiantes (Murphy, 2002).…”
Section: Discusión Y Conclusionesunclassified
“…Many things could go wrong during this period in cases of poor teaching and learning provision. For example, Muthivhi (2010) and Muthivhi and Broom (2009) studied concrete operational and formal operational learners whose learning was characterized by the forms of teaching that did not prepare them adequately for; and elaborate on, the reflective processes necessary for successful learning of the formal subject matter knowledge. These studies found that, although these learners demonstrated levels of performance consistent with normal developmental stages, they tended to be overreliant on concrete manifestations of the tasks and often derived conclusions to problems from their perceptions of the concrete situation rather than from their conceptualizations of the situation; taking full account of all available information to arrive at valid conclusion.…”
Section: Concrete Operational Stagementioning
confidence: 99%
“…activities (everyday-life activities that do not necessarily involve teaching), their elaboration and conscious application to problem situations may be constrained if classroom instruction does not foster their conscious application to problem situations (see, Muthivhi, 2010;Muthivhi and Broom, 2009;Shayer, 1997). For Piaget, the acquisition for this cognitive capacity demonstrates an important shift from self-centered, egocentric thought processes -where the child is not able to consider two or more relevant aspects of a situation to arrive at a valid conclusion -to a 'decentered', self-regulative and reflective form of thinking that characterizes operational thinking of school-going children.…”
Section: Major Developmental Stagesmentioning
confidence: 99%